An Interdisciplinary Approach to Historic Diet and Foodways: The FoodCult Project - Flavin, Susan (My University, 2021)
This research note introduces the methodology of the FoodCult Project, with the aim of stimulating discussion regarding the interdisciplinary potential for historical food studies. The project represents the first major attempt to establish both the fundamentals of everyday diet, and the cultural ‘meaning’ of food and drink in early modern Ireland, c 1550-1650. This was a period of major economic development, unprecedented intercultural contact, but also of conquest, colonisation and war, and the study focusses on Ireland as a case-study for understanding the role of food in a complex society. Moving beyond the colonial narrative of Irish social and economic development, it enlarges the study of food and identity to examine neglected themes in Irish historiography, including gender, class and religious identities, as expressed through the consumption of food and drink. Taking advantage of exciting recent archaeological discoveries and the increased accessibility of the archaeological evidence, the project develops a ground-breaking interdisciplinary approach, merging micro-historical analytical techniques with cutting-edge molecular science, experimental archaeology, data modelling and statistical analysis, to examine what was eaten, where, why and by whom, at a level of detail previously deemed impossible for this period in history. This overview provides a framework to facilitate the interpretation of descriptive literary, visual, and other representative historical sources for diet, building a bridge between ideas and practises in the development of early modern foodways. The project will lead to unparalleled collaboration across the sciences and humanities, serving as a model for future comparative interdisciplinary work across diverse chronologies and regions.
PUBLISHED
Keywords: Ireland; Interdisciplinary; Food history; Foodways; Early modern; Identities in Transformation; Making Ireland; History